“Estudio Jurídico y Doctrinario de la imputabilidad penal de los sujetos activos de los delitos de Incendios forestales.” - Vargas Espinosa, Mayury Vanesa (2025)
This curricular integration work focuses on the problem of forest fires in Ecuador, highlighting the weaknesses of the legal framework and public policies that are mostly oriented to protect the environment without adequately considering the circumstances for the criminal liability of the active subjects in cases of mental illness that cause these disasters, as well as taking into account the seriousness of the damage to biodiversity. Through interviews with environmental specialists and surveys of legal professionals, the barriers faced by the criminal justice system are identified and guidelines are proposed to help improve the situation. One of the most significant findings is that the legal system does not adequately guarantee the protection of the rights of nature, from its very lenient sanctions, to the adjudication of the criminal liability of offenders and the lack of awareness of the damages caused. Weaknesses in the legal framework contribute to the impunity of these acts, which in turn affects society as a whole, as well as the ecosystem's resilience and social security. Emphasis is placed on the need for a change in the legal and social approach to ensure that all perpetrators, regardless of conditions, are duly prosecuted and proportionally sanctioned. The paper proposes several specific objectives, among them, the need to present guidelines to promote public policies that guarantee criminal liability in cases of forest fires. It is suggested the comprehensive training of justice operators in the evaluation of these cases, in order to break stereotypes about the perpetrators and improve attention to the victims of these disasters. The creation of units specialized in the investigation of these acts within judicial institutions, ensuring an adequate and sensitive approach to the causes and consequences of these events. The importance of developing comprehensive prevention programs that include environmental protection measures, reforestation and awareness campaigns that seek to educate people about the risks and consequences, as well as individual responsibility. Interviews with professionals in the field lead to a consensus on the need for a change in the strictness of penalties for these crimes and their circumstances, as well as taking into account the amount of biodiversity lost.